IMPROVING THE DIDACTIC SYSTEM OF GENDER CULTURE DEVELOPMENT IN ADOLESCENT STUDENTS THROUGH GAMES - Alibekov Dilshod Islamovich (Zeta Repository, 2023)
This article analyzes the socio-pedagogical factors that shape modern forms of gender culture, emphasizing the need to form a culture of gender-specific roles, relationships and behaviors in each of the adolescent boys and girls. Keywords: gender culture, popular culture, national culture, adolescent students, social roles, pedagogical factors, gender conflicts, behavioral norms, value orientations, gender consciousness.